The Reality Of The Use Of Educational Technology And Modern Teaching Methods By The Teachers At Imam Al-Kadhim College (Journal of the College of Basic Education, 2022)
This study aimed to know the reality of the use of teaching staff in Imam Al-Kadhim College (peace be upon him) for educational technology and modern programs, and to reveal the differences in the use of communication and educational technology according to the gender variable, to enhance professional competencies and to keep pace with the rapid developments of educational technology and how to use it in the educational process at Imam Al-Kadhim College. (P) And the availability of standards, methods, modern teaching methods, and trends on which the field of educational technology is based at Imam Al-Kadhim College, and the identification of the most important difficulties faced by the teachers using educational technology and modern teaching methods. The number of (73), 55 males and 18 females, used a questionnaire by referring to previous studies and the theoretical framework. The questionnaire consisted of 26 items in two areas (the use of educational technology, the use of modern teaching methods) and statistical data analysis (SPSS) through Using percentage, arithmetic mean, t-test for one sample, t-test for two independent samples, and Facronbach to measure honesty and reliability. It was concluded that most of the teachers use information technology and modern electronic programs. There are no statistically significant differences between the two teachers in terms of gender (male or female), and the researcher has reached many recommendations and suggestions.